The Role of Fathers and the Father-child Interaction in Family Decision-making: A French Investigation - Rollet, Manon (2012)
This study aims to investigate the role of fathers and the father-child interaction in family decision-making through a primary contextualisation of the issues around this topic that are further developed throughout the dissertation. In particular, a review of the concepts of family and family decision-making and an overview of the consumer socialization aspect of the father-child interaction are first conducted. Then a description of the communication and the influences strategies among family members and the portrayal of fathers and by extension mothers are carried out to provide a complete backdrop of the overall subject. The data from seven interviews of fathers of children under the age of seven are collected for an interpretative thematic analysis. The results demonstrate a reported more balanced division of labour and childcare between spouses, a relative impact of the change in women’s occupational status on fathers’ schedule and the anchored albeit richer role of fathers through the contrast with research on motherhood.